2019
DOI: 10.1002/brb3.1412
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hamartomas in adulthood: Clinical spectrum and treatment outcome—A unicenter experience

Abstract: IntroductionClinical manifestations of the hypothalamic hamartoma‐epilepsy syndrome (HH‐ES) in adulthood are variable. Efficacy of therapeutic options and outcome are diverse.MethodsRetrospective study of adult patients diagnosed with a HH in magnetic resonance imaging and epilepsy who attended our tertiary Epilepsy Unit between 2003 and 2018. We report the clinical and electroencephalographic features of a series of adult patients with HH and related epilepsy seen in our center together with the treatments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Both our results and those of prior studies have shown that small HH lesions generally exhibit reduced epileptic severity and more gradual disease evolution. [19][20][21] As such, epileptiform activity within the HH has a higher chance of contributing to seizure onset and disease progression when a sessile attachment to the hypothalamus enables it to propagate to the diencephalon and various other cortical structures. 7,22 Over the course of epilepsy evolution, many other seizure types generally develop in patients following initial GS presentation after a delay, 2,6 with these seizures being linked to ictal discharges affecting a range of neocortical areas but sparing the HH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both our results and those of prior studies have shown that small HH lesions generally exhibit reduced epileptic severity and more gradual disease evolution. [19][20][21] As such, epileptiform activity within the HH has a higher chance of contributing to seizure onset and disease progression when a sessile attachment to the hypothalamus enables it to propagate to the diencephalon and various other cortical structures. 7,22 Over the course of epilepsy evolution, many other seizure types generally develop in patients following initial GS presentation after a delay, 2,6 with these seizures being linked to ictal discharges affecting a range of neocortical areas but sparing the HH.…”
Section: Discussionmentioning
confidence: 99%
“…Both our results and those of prior studies have shown that small HH lesions generally exhibit reduced epileptic severity and more gradual disease evolution. 19 , 20 , 21 As such, epileptiform activity within the HH has a higher chance of contributing to seizure onset and disease progression when a sessile attachment to the hypothalamus enables it to propagate to the diencephalon and various other cortical structures. 7 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…HH occurs concurrently with precocious puberty in 63% of patients, epileptic seizures in 61%, and both in 25%. 4 5 …”
mentioning
confidence: 99%